STUDY OF BROMINATION REACTION OF 2,2,3,6,6-PENTAMETHYL-1,7-DIOXASPIRO[4,4]NONEN-3-ONE-8 AND THE SYNTHESIS OF NEW DERIVATIVES OF SPIROLACTONES ON THE BASE OF 3-BROMOMETHYL DERIVATIVE (Proceedings of the YSU B: Chemical and Biological Sciences, 2012)
Bromination reaction of 2,2,3,6,6-pentamethyl-1,7-dioxaspiro[4,4]no-nen-3-one-8 with molecular bromine and N-bromsuccinimide has been studied. New derivatives of spirolactones have been synthesized on the base of 3-bromomethyl derivative.
Keywords: bromination; spirolactones; N-bromsuccinimide; 3-bromomethyl derivative